Marketing Program : Brand Audit Alumni Study - Thomas, Dylan; Peterson, Jacob; Swanson, Scott R. (My University, 2017)
The research being presented is part of a brand audit of the UW-Eau Claire Marketing unit. The study involved collecting both qualitative and quantitative data from UWEC marketing alumni (n=349) using an on-line questionnaire. Findings capture alumni satisfaction ratings on a number of important program variables and identifies respondent perceptions of how well they were prepared for the marketplace.
Color poster with text, graphs, and charts.
Keywords: University of Wisconsin--Eau Claire; Alumni; Brand audit; Marketing; Posters